Full employment as a permanent policy response to poverty - Tomczak, Stephen Monroe; Rofuth, Todd W. (Journal of Community Practice, 2015)
Rising inequality and concomitant economic insecurity and poverty is a continuing problem in the United States today. Enacting full employment policies would resolve this problem and would serve as a viable poverty reduction strategy. Using a more accurate measure of unemployment such as the Bureau of Labor Statistics U-6 measure would reveal the true unemployment rate. This article provides different strategies, historical and more recent, for enacting full employment with a living wage, particularly the enactment of a permanent national public service employment program administered by the states through the TANF Emergency Fund. Public sector employment expansion in the green or clean economy would benefit the urban unemployed the most. To achieve these ends, social workers, unions and community activists will need to collaborate. Finally, the Federal Reserve should review the history of the relationship between unemployment and inflation rates and develop a more accurate formula for attaining full employment while keeping inflation low. Copyright © Taylor & Francis Group, LLC.
Keywords: United States; dept.swk; economic inequality; emergency; employment; full employment; human; human experiment; peer-reviewed; policy; poverty; social worker; statistics; unemployment

Hunger in a “Land of plenty”: A renewed call for social work action - Libal, Kathryn; Tomczak, Stephen Monroe; Spath, Robin; Harding, Scott (Social Work, 2014)
Keywords: Child; Cooperative Behavior; Cross-Sectional Studies; Financing, Government; Food Assistance; Food Supply; Forecasting; Humans; Hunger; Interdisciplinary Communication; Politics; Poverty; Social Welfare; Social Work; Socioeconomic Factors; United States; catering service; child; cooperation; cross-sectional study; dept.swk; economics; financial management; food assistance; forecasting; human; hunger; interdisciplinary communication; organization and management; politics; poverty; social welfare; social work; socioeconomics; statistics and numerical data; trends